Fill Arís : Oidhreacht Sheáin Uí Ríordáin. - Mac Amhlaigh, Liam (Cló lar-Chonnacht, 2012)
This volume contains a series of lectures from the conference to commemorate the poet, Seán Ó Ríordáin, on the thirtieth anniversary of his death, which was organised by the staff in the department of Modern Irish in the School of Irish, Celtic, Folklore and Linguistics in University College Dublin.